Journeying Through Inquiry-Based Learning: A Focus on Science Process Skills - Saleh, Andi Rahmat; Hala, Yusminah; Ramadani, Rani (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
This research is a quasi-experimental study with a pretest posttest control group design. This study aims to determine the influence of the guided inquiry learning model on the science process skills of students in class XI MIPA on motion systems material. This research was carried out at SMA Negeri 1 Kodeoha, Southeast Sulawesi in 2022/2023 academic year. The study took XI MIPA 1 as experimental class and XI MIPA as the control class. Each class consisted of 30 students. Sample selection was done by random sampling. In the experimental class, the guided inquiry learning model was applied while in the control class was implemented direct instruction model. The results of the science process skills test using the t-test obtained t-count of 2.6837 and t-table at a significant level (α = 0.05) of 2.0484, so t-count > t-table. It can be concluded that there is an influence of the guided inquiry learning model on the science process skills of XI MIPA class students on motion systems material at SMA Negeri 1 Kodeoha, Southeast Sulawesi.